25 years of publishing "Knygotyra" - Stonienė, Vanda (Knygotyra, 1988)
The first volume of "Knygotyra" ("Book Science") was published in 1961 under the title "Bibliotekininkystės ir bibliografijos klausimai" ("Aspects of Librarianship and Bibliography"). From 1970 onwards (beginning with volume 8), it adopted the new title "Knygotyra," along with a new double numbering system—1(8). Starting from volume 8(15), the publication was divided into two separate thematic editions: the first focused on historical subjects, and the latter on modern problems of bibliology, librarianship, bibliography, and informatics. During its 25 years of publication history, "Knygotyra" has published 256 research articles, 35 archival documents, and 25 book reviews. Most contributors to the edition come from the scientific and teaching staff of Vilnius State University and the main libraries of Lithuania. Additionally, contributors include individuals from Latvia, Estonia, Belarus, East Germany (GDR), Moscow, and Leningrad (the contributors are listed in Tables No. 1 and 2, with the subject index in Table No. 3). The greatest attention in the publication has been given to the history of the Lithuanian book. Future editions should focus more on the problems of book functioning in society, analysis of the external appearance of books, statistics, etc. In Lithuania, "Knygotyra" was a pioneer in publishing articles on informatics and information activities. Not only librarians and book science researchers, but also historians and literary critics, have shown repeated interest in the archival documents published in "Knygotyra." The publication of archival documents should be expanded, as should book reviewing. "Knygotyra" is available in any Lithuanian library. Additionally, the Department of Exchange at the Vilnius University Library distributes it to 87 libraries across the Soviet Union and foreign countries. It is regularly sent to 34 libraries in socialist countries and 12 other foreign countries (including 10 libraries in the USA).